Kulturowo-​obiektywne istnienie procesu komunikacji jako warunek projektowania autonomicznej dyscypliny komunikacji - Kulczycki, Emanuel (Instytut Kulturoznawstwa Uniwersytetu Marii Curie-Skłodowskiej, 2011)
The purpose of the present paper is to suggest a philosophical basis for reflection about communication and considerations about disciplinary status of this reflection. The article is an attempt at showing conditions which have to be fulfilled to achieve non-institutional autonomization of communication research. The most important conclusion that is drawn here is that the process of communication must be seen (by researchers) as existing in a culturally objective way (intersubjective).
Keywords: Komunikacja; Komunikologia; Ontologia komunikacyjna; Filozofia kultury